2015
DOI: 10.1089/pho.2014.3792
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometric Assessment of the Influence of Low-Level Laser Therapy on Peri-Implant Tissue Healing in the Rabbit Mandible

Abstract: Objective: The purpose of this study was to demonstrate the effect of low-level laser therapy (LLLT) on the peri-implant bone healing process in the rabbit mandible. Background data: LLLT has been shown to accelerate tissue repair and osseointegration of implants placed into the rabbit tibia. However, the beneficial effects of LLLT have never been tested in the rabbit mandible, which would more closely mimic the human situation. Materials and methods: Twenty-four male New Zealand rabbits were randomly divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 29 publications
1
17
0
1
Order By: Relevance
“…For instance, three papers looked at peri-implant bone regeneration after PBM. Menezes et al 98 found that 20 J∕cm 2 was the best dose to deliver, whereas Massotti et al 22 and Mayer et al 23 found that 20 J∕cm 2 was the worst dose to deliver.…”
Section: Fluence and Irradiancementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, three papers looked at peri-implant bone regeneration after PBM. Menezes et al 98 found that 20 J∕cm 2 was the best dose to deliver, whereas Massotti et al 22 and Mayer et al 23 found that 20 J∕cm 2 was the worst dose to deliver.…”
Section: Fluence and Irradiancementioning
confidence: 99%
“…[16][17][18] Doses for deeper-seated targets should be in the 10 to 50∕cm 2 range. [19][20][21] While many studies have shown a positive effect of PBM, 17,18,21 a number have failed to show a benefit 22,23 and, in fact, some reports have shown negative outcomes at what are reported to be the same parameters of irradiation as other positive studies. Unfortunately, in many of the historical studies, important laser parameters were omitted or incorrectly presented.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies reported positive effects in terms of promotion of bone formation around Ti implants, and higher bone implant contacts (BICs) were reported ( Table 1). [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Many researchers have confirmed that low-level light therapy can promote bone formation by stimulatory effects on osteoblasts, which can lead to greater osteo-integration of Ti implants. This has been evaluated in different study designs and laser irradiation parameters.…”
mentioning
confidence: 99%
“…Rabbit, dental implant placement 2015 Massotti et al 45) ・830 nm ・5, 10, 20 J/cm 2 ・every 48 h for 13 days after the extraction 1) Control 2) LLLT (5 J/cm 2 ) 3) LLLT (10 J/cm 2 ) 4) LLLT (20 J/cm 2 ) histological analysis Histomorphometric evaluation showed significantly higher bone-to-implant contact and significantly more collagen fibers in LLLT at 20 J/cm 2 group.…”
Section: ) Control 2) Lllt 3) Mscs/bone Grafts 4) Mscs/bone Grafts +mentioning
confidence: 99%